2008
DOI: 10.1016/j.joca.2008.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Should subchondral bone turnover be targeted when treating osteoarthritis?

Abstract: Objective: Osteoarthritis (OA) is the most common form of arthritic disease, and it is a major cause of disability and impaired quality of life in the elderly. OA is a complex disease of the entire joint, including bone and cartilage, thereby presenting alternative approaches for treatment. This review summarizes emerging observations from cell biology to preliminary clinical trials, describing interactions between the bone and cartilage components. We speculate whether a treatment for OA would be possible wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(151 citation statements)
references
References 103 publications
4
143
0
4
Order By: Relevance
“…(37) The tidemark, which was thought previously to be a strict barrier between cartilage and bone, allows perfusion of chemo-and cytokines released by the diseased chondrocytes and inflamed synovial tissue. (38) In line with this assumption is that if mechanics instead of chemical components would be involved, a compensatory increase in bone tissue is anticipated owing to the loss of the mechanical function and with that shock absorbance of the cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…(37) The tidemark, which was thought previously to be a strict barrier between cartilage and bone, allows perfusion of chemo-and cytokines released by the diseased chondrocytes and inflamed synovial tissue. (38) In line with this assumption is that if mechanics instead of chemical components would be involved, a compensatory increase in bone tissue is anticipated owing to the loss of the mechanical function and with that shock absorbance of the cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is increasingly accepted that subchondral bone plays an important role in the pathogenesis of OA. Accumulating evidence from clinical and animal studies has demonstrated that during OA progression, subchondral bone turnover increases dramatically, with increased bone resorption occurring early, and increased bone accretion occurring later in the disease [6][7][8] . Meanwhile, the biochemical composition and biomechanical properties of the subchondral bone are altered [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…The increased stress thereby imposed on the other components of the joint complex usually triggers a process of tissue remodeling, which, by altering the loading dynamics of the joint, exacerbates rather than alleviates the disease symptoms [18,21]. Furthermore, the pain and restricted ROM associated with OA necessitate changes in the pattern of loading by the affected individual, which further complicate the development of the disease.…”
Section: Introductionmentioning
confidence: 99%